(untitled) (Research, Society and Development, 2021)
Multifunctional microorganisms are beneficial microorganisms that have direct and indirect mechanisms for promoting plant growth and play an important role as an alternative technology towards scale for sustainable agriculture. The increase in demand for agricultural production with a significant reduction in the use of synthetic fertilizers and pesticides is a major challenge today. The study of these microorganisms has been highlighted in recent years due to the great demand for sustainable technologies, which may reduce production costs, increasing the productivity and profitability of agribusiness. The application of multifunctional microorganisms through direct and indirect mechanisms has shown that it is possible to make crop management practices more environmentally sustainable. The mechanisms of multifunctional microorganisms include the regulation of hormonal balance, solubilization of nutrients in the soil solution and induction of resistance against pathogens. The objective of the work was to bring information regarding multifunctional microorganisms prioritizing the general aspects, the characteristics of the microorganisms (rhizobacteria and fungi) that promote plant growth and their main mechanisms of action. In summary, it is concluded that multifunctional microorganisms have several favorable characteristics to be used as promoters of plant growth in sustainable agriculture.